IMPLEMENTASI MODEL PENGAJARAN TEAM TEACHING METHOD (TTM) - I Wayan Ratha Adhi Kesuma (Pascasarjana Universitas Hindu Indonesia, 2016)
The concept of learning with a model called Team Teaching Method (TTM) is considered representative to apply. TTM is a method of teaching in which some teachers are collaboratively participating together to provide the material aimed at changing the learning ambience expected to have implications in increasing the students’ motivation on the Hinduism subject. The result of the analysis towards the teachers’ activity in preparing a learning scenario and in managing the classroom based on the observation on the cycle I up to the cycle II indicates significant increase. In other words, the application of learning model of TTM has a positive impact on improving the competence of the teachers in preparing and presenting innovative learning.